ANTIBIOTIC SUSCEPTIBILITIES OF GRAM NEGATIVE AEROBIC BACTERIA ISOLATED FROM URINARY TRACT INFECTIONS IN COMMUNITY (Iraqi Journal of Medical Sciences, 2016)
Background: Urinary tract infection (UTI) caused by bacteria that can also live in the digestive tract, in vagina, or around the urethra most often these bacteria, enter the urethra and travel to the bladder and kidneys and prostate (in men).Objective: To determine the most common gram negative aerobic bacteria caused UTI in both sex and different ages, and to study the antibiotic susceptibility in order to determine the most effective antibiotics that can cure UTI.Methods: Prospective study of 311 samples of urine has been collected from out patients complaining signs and symptoms of UTI. Isolation and Identification of causative bacteria was concluded, antibiotic susceptibility test has been done, and statistical analysis chi square had done. Results:125 urine samples obtained from 25 male and 100 female show growths of Gram negative aerobic bacilli. No bacterial growth was defined in the rest of urine samples. Single bacterium was identified in 120 samples, while 5 samples identified as a mixed infection with two kinds of bacteria. In 55 (44%) of cases, Echerishia Coli was isolated; in 41 (32.8%) Klebsiella Pneumoniae; in 17 (13.6%) Proteus mirabilis plus P. Vulgaris; and 12 (9.6%) Pseudomonas aeruginosa. The percentage of resistance for E. Coli varies from 73% to 86%, to Ceftzidime, Ceftriaxone, and Trimethoprim Sulfamethaxozol; for K. pneumoniae it ranges from 71% to 100% for Amoxicillin, Pipracillin, Trimethoprim Sulfamethaxozole, and Colistin; for P. mirabilis plus P. vulgaris ranging from 66% to 100% for Cetazidime, Trimethoprim Sulfamethaxozol, and Cefotaxime; and for P. aeruginose ranges from 66% to 100% for Cefazidime, Colistin, Nafcillin, Gentamycin, Trimethoprim Sulfamethaxozol.Conclusion: E. Coli caused UTI in female higher than men in the community, and the gram negative rods had multi antibiotic resistant.Keyword: UTI, Enterobacteriacae, Antibiotic susceptibility
Keywords: UTI; Enterobacteriacae; Antibiotic susceptibility